Status of Sri Lankan culture-based fisheries: an overview - Amarasinghe, U.S. (Australian Center for International Agricultural Research, 2026)
In Sri Lanka, due to the extensive availability of productive reservoir resources, there is a high potential for the development of CBF. With concerted research and development efforts on this fisheries enhancement strategy, CBF development in inland reservoirs is gaining momentum. In small village reservoirs of the country, there are no established fisheries and as such, CBF development in such reservoirs involves mobilising agricultural farmers to adopt this activity. In perennial reservoirs on the other hand, where there are established fisheries, fishers should be motivated to adopt CBF technologies. Giant freshwater prawn, Macrobrachium rosenbergii, is also used for CBF development in many reservoirs. Presently, freshwater prawn is caught as incidental catch in gillnets targeting finfish varieties. It is necessary to introduce an effective method of harvesting freshwater prawn, such as traps. Optimal stocking densities in relation to biological productivity of water bodies, post-harvest product qualities, bioeconomic aspects of CBF, value chain analysis, gender-related aspects and livelihood analysis, are the aspects that are effectively addressed by the research and development (R&D) project of ACIAR. Most importantly, there should be strategies for addressing the issue of fingerling scarcity, and for strengthening the extension mechanism of the National Aquaculture Development Authority (NAQDA) to introduce effective co-management for sustainability of CBF in Sri Lankan reservoirs
Keywords: Freshwater prawns; Water resources; Fisheries; Irrigation reservoirs; Aquatic environment